Attitudes toward preimplantation genetic testing for aneuploidy among patients with recurrent pregnancy loss in Japan. Issue 4 (7th February 2020) - Takeda, Eri; Sugiura‐Ogasawara, Mayumi; Ebara, Takeshi; Kitaori, Tamao; Goto, Shinobu; Yoshihara, Hiroyuki; Sato, Takeshi
Abstract: Aim: To examine attitudes toward preimplantation genetic testing for aneuploidy (PGT‐A) in patients with recurrent pregnancy loss (RPL) because it has been performed worldwide in spite of little evidence regarding whether it can improve the live birth rate and prevent miscarriage. There has been no study to examine attitudes toward PGT‐A in patients with RPL. Methods: We conducted a cross‐sectional study that used a questionnaire to examine attitudes toward PGT‐A, the desire for PGT‐A and the factors associated with this desire in 386 patients with RPL between November 2014 and January 2019. Results: Overall, 25.1% of patients desired PGT‐A and 35.2% answered that they knew about it. Regarding the reasons for wanting PGT‐A, 42.3% thought that it would insure a live birth and with complete case analysis, showed that the patients' wish for PGT‐A as a means of giving live birth was affected by their IVF‐ET history (adjusted odds ratio 2.7, 95% CI 1.2–7.2) and whether they had any knowledge of PGT‐A (2.4, 1.1–5.3). Those with a higher total family income (3.5, 1.2–10.1) and a previous IVF‐ET (4.6, 2.0–10.3) tended to want PGT‐A as a means of avoiding miscarriage. Conclusion: The majority had no opinion or a poor knowledge of PGT‐A. More patients who self‐assessed as knowing about PGT‐A or who had undergone IVF‐ET had the above type of misunderstanding. Accurate and up‐to‐date information from facilities different from those in which PGT‐A is performed is necessary before reaching a decision on PGT‐A.